A survey and evaluation of available economic time series which are related to building activity with special reference to their prognostic value - Martin, Charles Henry (Stellenbosch : Stellenbosch University, 2012)
Thesis (M.Sc. (Agric)) -- University of Stellenbosch, 1981.